Molecular subtyping of Blastocystis sp. isolates from humans and animals in the Senoi and Proto-Malay tribes of Orang Asli, Pahang / Nabilah Amelia Mohammad - Mohammad, Nabilah Amelia (2017)
Infection by the parasite with unsettled clinical significance; Blastocystis is a common health problem in developing countries. The genetically diverse parasite currently classified into 17 subtypes (STs) with human isolates categorised into ST1 to ST9. Infections with genotypic homology animal isolates are demonstrated in all of these nine subtypes. Hence, this study was undertaken to comprehensively determine the subtype distributions, zoonotic potential and pathogenicity of the parasite in 359 stool samples obtained from the Senoi and Proto-Malay tribes and animals from Sungai Lembing, Pahang. Samples were examined for the presence of Blastocystis using microscopic techniques (Wheatley's trichrome stain and in-vitro culture) and PCR assay. Demographic and socioeconomic data were collected using standardised questionnaire. Amplicons of 550 to 585-bp of the SSU rRNA gene were purified, sequenced and phylogenetic tree was constructed using maximum likelihood method in MEGA6. Among Orang Asli isolates, ST3 (9.5%) was the predominant subtype, followed by ST1 (5.5%), and ST2 (2.8%). ST2 (1.0%) and ST10 (11.3%) were detected in macaque and deer, respectively. ST3 was commonly found in symptomatic (6) and asymptomatic (18) individuals, thus, its pathogenic potential remains controversial. These findings deduced that Blastocystis is still prevalent among Orang Asli and animals. It also highlights the possible zoonotic risks as ST2 was found in both hosts. In addition, combination of both microscopic techniques are more superior (K = 0.353) than individual technique. Nevertheless, these informations may be beneficial to reassess the existing intervention strategies. It is hoped to prevent future expansion of the parasite hence significantly improve the quality of life and health of Orang Asli.